Site-directed mutagenesis of the nitrogenase MoFe protein of Azotobacter vinelandii - Brigle, Kevin E. (1987)
A strategy has been formulated for the site-directed mutagenesis of the Azotobacter vinelandii nifDK genes. These genes encode the α and β subunits of the MoFe protein of nitrogenase, respectively. Six mutant strains, which produce MoFe proteins altered in their α subunit by known single amino acid substitutions, have been produced. Three of these transversion mutations involve cysteine-to-serine changes (at residues 154, 183, and 275), two involve glutamine-to-glutamic acid changes (at residues 151 and 191), and one involves an aspartic acid-to-glutamic acid change (at residue 161). All three possible phenotypic responses are observed within this group— i.e., normal, slow, and no growth in the absence of a fixed-nitrogen source. Two-dimensional gel electrophoresis indicates that all mutants accumulate normal levels of the subunits of both nitrogenase component proteins. Whole-cell and crude-extract acetylene-reduction activities indicate substantial levels of Fe protein activity in all strains. In contrast, MoFe protein activities do not parallel the diazotrophic growth capability for all strains. Two strains appear to exhibit altered substrate discrimination. Such analyses should aid in the identification of metallocluster-binding sites and subunit-subunit interaction domains of the MoFe protein and also provide insight into the mechanistic roles of the various prosthetic groups in catalysis.